The Democratic Turn Democracy Between Closure and Indeterminacy - Paul Blokker (lo Squaderno, 2008)
Since the disappearance of most of ‘really existing socialism’ with the regime changes in the Soviet world, one can often hear the argument that now liberal democracy is the only viable form the polity can take in modernity (the most obvious and well-known - but surely not only - thesis in this regard is Francis Fukuyama’s The End of History, 1989: ‘The triumph of the West, of the Western idea, is evident first of all in the total exhaustion of viable systematic alternatives to Western liberalism’).